2017
DOI: 10.12965/jer.1734952.476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-week core stabilization exercise on the Cobb angle and lumbar muscle strength of adolescents with idiopathic scoliosis

Abstract: To identify the effects of core stabilization exercise on the Cobb angle and lumbar muscle strength of adolescent patients with idiopathic scoliosis. Subjects in the present study consisted of primary school students who were confirmed to have scoliosis on radiologic examination performed during their visit to the National Fitness Center in Seoul, Korea. Depending on whether they participated in a 12-week core stabilization exercise program, subjects were divided into the exercise (n=14, age 12.71±0.72 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 29 publications
(28 reference statements)
0
42
0
3
Order By: Relevance
“…Based on the above discussion, there is a need for a recommendation that patients with AIS, irrespective of curvature severity, are encouraged to participate in sports and regular PA. Unfortunately, most of the studies assessing the effect of therapeutic spinal exercises in patients with AIS only include mild severity cases [ 43 , 44 ]. A recent meta-analysis based on the outcome of 15 studies has reported that the effect of therapeutic Schroth exercises is more beneficial for Cobb angles < 30° [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above discussion, there is a need for a recommendation that patients with AIS, irrespective of curvature severity, are encouraged to participate in sports and regular PA. Unfortunately, most of the studies assessing the effect of therapeutic spinal exercises in patients with AIS only include mild severity cases [ 43 , 44 ]. A recent meta-analysis based on the outcome of 15 studies has reported that the effect of therapeutic Schroth exercises is more beneficial for Cobb angles < 30° [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of scoliotic dancers with these common and desired characteristics are probably the end result of a rigorous selection process [6,18]. Other physical features such as reduced muscle strength [19] and reduced postural balance [20] were found to be associated with scoliosis, yet these studies reported only on adolescent non-dancer populations.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed significant improvement in the total ATR when comparing pretreatment measurements to those obtained after 24 weeks of treatment. Many studies have obtained similar results in the improvement of ATR after the application of different treatment exercise methods, especially Schroth exercises [5,17,18,[41][42][43].…”
Section: Discussionmentioning
confidence: 79%